Effect of Alcoholic Extract of Al qinnabry Plant Cardaria draba (L.) Desv. on the dwarf tape worm Hymenolepis nana: T.I. Alalousi ; D.A.M. Alsawah ; Saadiah S.H. Alobaidi - Alalousi, T. I. (The Iraqi Journal of Veterinary Medicine, 2006)
This study involved effect of alcoholic extract of Cardaria draba (L.) Desv.Plant on Hymenolepis nana at dose (50,100,250) mg/ml respectively andacomparison between effect of the extract and mebendazole drug in allexperiments. The results of these experiments were indicated that the out putrates of the egg of H. nana in the Faeces were effected the efficacy of extractsand drug treatments were varied in the daily counts through the experiments andit appeared that they were proportional increasing with the increasing of the dosethey are (91.5%, 86.7%, 86.2%) on days (8, 9, 10) at (250) mg / kg dose for theFresh plant and (89.7%,87.7%,83.9%) for the drug part respectively. Themebendazole drug appeared the effect ivness comparing with the extractefficiency was (100%) in the fifth day at (250) mg / kg. After the oraladministrating the maxture off egg and plant extracts for the mice, the effect ofextracts was evident on the growth and the development of the eggs. Thenumber of eggs increased according to the dose raising the patient period weredelayed about of the 4 days by using (250) mg / kg of the extracts. Further more,the number of eggs were decreased at the same doses of the fresh and dryextracts, when the count were (110, 100) eggs/gram of faeces respectively, incomparing with control group the effect of mebendazole drug was more thanthat of the extracts in that patient periods was delayed for (8) days in theconcentration of (250) mg/kg the output of the eggs was decreased to low levelscomparing with extracts and control group.